Eco-friendly synthesis and potent antifungal activity of 2-substituted coumaran-3-ones - PRABHA SOLANKI; PRACHI SHEKHAWAT (Smujo International, 2012)
Abstract. Solanki P, Shekhawat P. 2012. Eco-friendly synthesis and potent antifungal activity of 2-substituted coumaran-3-ones. Nusantara Bioscience 4: 101-104. 3-halochromones (IIa-c and IIIa-c) have been synthesized by treating 1- (2-hydroxyphenyl)-3-methyl-1,3-propanediones (Ia-c) with bromine or sulphuryl chloride in dioxane respectively. These chromones were employed in the synthesis of 2-acetyl-coumaran-3-ones (IVa-f). These were subjected to Knoevenagel condensation to give 2-cinnamoyl coumaran-3-ones. In vitro assay and field trials of these compounds against Fusarium oxysporum were carried out to study the antifungal effect of target compounds. Compound Va was the most effective growth inhibitor of the pathogen, whereas Vc showed a little tendency and Vb, Vd, Ve and Vf hardly inhibit the growth.